2014
DOI: 10.2147/rrn.s52377
|View full text |Cite
|
Sign up to set email alerts
|

Role of effective thermoregulation in premature neonates

Abstract: Even though researchers have studied ways to reduce heat loss in premature infants for more than 100 years, hypothermia remains a widespread problem in this population, especially after birth and through the first weeks of life. This review focuses on current research findings that are being translated into practice to reduce heat loss after birth and during neonatal intensive care unit hospitalization. Recommendations for practice are given to minimize heat loss during care and promote thermal stability for v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 47 publications
0
10
0
4
Order By: Relevance
“…An under‐developed thermoregulatory system predisposes sick and preterm infants to increased hypothermic risk . For this reason, well‐supported evidence‐based thermal management practices exist in the NICU and these translate to high rates of normothermia in the NICU.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An under‐developed thermoregulatory system predisposes sick and preterm infants to increased hypothermic risk . For this reason, well‐supported evidence‐based thermal management practices exist in the NICU and these translate to high rates of normothermia in the NICU.…”
Section: Discussionmentioning
confidence: 99%
“…Neonates are at particular risk of unintentional hypothermia, which is associated with significant harmful consequences, leading to increased morbidity and mortality . Accordingly, thermoregulatory management has long been a central tenet of neonatal intensive care, with a myriad of solutions available.…”
mentioning
confidence: 99%
“…Moreover, it isn't a handy device in resource-limited settings such as developing countries. The warm moist environment of the incubator represents an ideal media for bacteria to proliferate which increases the risk of staphylococcal infection [38]. A recent systematic review concluded that there is no risk of hyperthermia with synchronized use of incubators (5.4% with incubator use, 8.1% without, RR = 0.66; 95% CI 0.19 to 2.3) [24].…”
Section: Skin-to-skin Contact (Ssc)mentioning
confidence: 99%
“…Moreover, it isn't a handy device in resource-limited settings such as developing countries. The warm moist environment of the incubator represents an ideal media for bacteria to proliferate which increases the risk of staphylococcal infection [38] 6]., respectively; P < .0001) [39]. A randomized controlled trial that compared between HHG and cold dry gas concluded that in the HHG group, 69% of preterm neonates were normothermic compared with 55% in the cold, dry gas group (unadjusted OR 1.8, 95% CI 1.01-3.19) [40].…”
Section: Skin-to-skin Contact (Ssc)mentioning
confidence: 99%
“…Sabe-se que este é um problema particularmente relevante nos RNPT, com idade gestacional igual ou menor do que 30 semanas, durante a primeira semana de vida, nos quais a evaporação é elevada devido ao aumento da perda de água transepidérmica (2,3) . O cuidado quanto à temperatura corporal do recém-nascido deve iniciar desde o nascimento, ainda na sala de parto, estendendo-se para todos os ambientes e etapas de seu internamento.…”
Section: Introductionunclassified